The Influence of Project-Based Learning on Entrepreneurial Crafts Learning Outcomes through Learning Independence - Artayasa, I Kadek; Parwata, I Gusti Lanang Agung; Ratnaya, I Gede (International Journal Labs, 2023)
Background: The development of learning independence is very necessary in the success of the learning process. Students who have high learning independence tend to learn better, are able to monitor, evaluate, and manage their study schedules effectively. More than that, students can estimate the time in working on the project. Aim: This study aims to examine the effect of the implementation of the project-based learning model on the learning outcomes of entrepreneurial crafts in terms of the learning independence of class X students. Method: This research is an experimental research with a factorial design method. The research data was obtained through a student learning independence questionnaire and also a student comprehension test. This study involved 32 students who were taken using a random sampling technique. The data were analyzed by using SPSS 26, by conducting descriptive statistical tests, prerequisite tests namely normality and homogeneity tests, and then tested research hypothesis using two-way Anova. Findings: Project-based learning models are more effective than direct learning models in improving learning outcomes. Project-based learning models provide positive interactions with students' independent learning. Learning outcomes of students with high learning independence shows a significant difference between the Project-based learning and direct learning model. The learning outcomes of students with low learning independence show a significant difference between the learning model of Project-based learning and direct learning model.